Ответы и объяснения

2013-12-12T17:49:19+04:00
62х-256=114-38х                                          351-92х=51-72х
62х+38х=114+256                                        351-51=92х-72х
100х=370                                                        300=20х
х=370:100                                                       х=300:20
х=3,7                                                                х=15

229-43х=62х-44                                           405+95х=-55+49х
-43х-62х=-44-229                                        95х-49х=-55-405
-105х=-273                                                    46х=-460
х=-273:-105                                                   х=-460:46
х=  2,6                                                               х=-10


17*(5+х)-20х=8х-14                                     29+14(9-у)=19-2у
85+17х-20х-8х=14                                       29+126 -14у+2у=19
-11х=14-86                                                   -12у=19-29-126
-11х=-72                                                        -12у=-136
х=-72:-11                                                        у=-136:-12
х=6,(54)                                                          у=-11,(3)


24х-12*(7+х)=16-8х                                   -15*(4у-3)+37у=42у-111
24х-84-12х=16-8х                                       -60у+45+37у=42у-111
20х=16+84                                                   -65у=-111-45
20х=100                                                        -65у=-156
х=100:20                                                        у=-156:-65
х=5                                                                  у=2  33/65